Abdominal Aortic Aneurysm Repair in Renal and Liver Transplant Recipients. (January 2020) - Premaratne, Sobath; Hopkins, Jonathan; Duddy, Martin; Tai, Ket Sang; Kay, Mark; Rogoveanu, Radu; Nicholl, Phil; Tiwari, Alok
Background: Abdominal aortic aneurysm (AAA) repair in patients with organ transplant remains a challenge. We looked at AAA repair in patients with organ transplants at our tertiary liver and kidney transplant unit. Methods: A retrospective analysis of a prospectively maintained database was undertaken from January 2008 to July 2018. We looked at patient demographics, type of repair, and technical success including reinterventions, perioperative transplant organ function, and 30-day and 1-year survival rate. Eight of 662 patients who underwent AAA repair had a solid organ transplant. Of these, 5 were kidney transplants, 2 liver transplants, and 1 had kidney and liver transplant; 75% were male; and average age was 63.4 (range: 49-83). All patients had asymptomatic AAAs, and 6 were treated with standard endovascular repair, 1 standard repair with iliac branch device, and 1 open repair. Adjunctive techniques such as CO2 angiograms, deployment of main body through contralateral iliac, low-profile sheaths, custom-made stent grafts, and temporary axillo-femoral shunting were used to protect transplant organs. Thirty-day survival was 100% with 1 death at 5 months from liver failure, and 1 patient has a persistent type-2 endoleak 3 years after the procedure. Conclusion: Abdominal aortic aneurysm repair in patients with organ transplants can be undertaken using adjunctive endovascular and open surgical techniques.